2012
DOI: 10.5539/ijb.v4n2p26
|View full text |Cite
|
Sign up to set email alerts
|

Different phenotypic and proteomic markers explain variability of beef tenderness across muscles

Abstract: This study analyzed the abundance of tenderness biomarkers: 24 proteins and 11 phenotypic carcass characteristics and muscle properties. This was done on 111 samples of two muscles, Longissimus thoracis (LT) and Semitendinosus (ST) from the Charolais cattle breed. The strategy was to constitute and explain three tenderness classes on the two muscles separately, on the shear-force data (Warner-Bratzler). Results showed that ST classes were explained by 12 proteins and 6 phenotypic characteristics. LT classes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 45 publications
8
30
0
3
Order By: Relevance
“…Fast and slow myosin heavy chain isoforms were also inversely correlated with tenderness in the two muscles. These results are in accordance with Picard et al (2007) and Guillemin et al (2012).…”
Section: Understanding the Underlying Mechanismssupporting
confidence: 95%
“…Fast and slow myosin heavy chain isoforms were also inversely correlated with tenderness in the two muscles. These results are in accordance with Picard et al (2007) and Guillemin et al (2012).…”
Section: Understanding the Underlying Mechanismssupporting
confidence: 95%
“…Several studies have found a relationship between meat tenderness and HSPs abundance [22, 36, 37]. Due to the highly conserved chaperone capacity of proteins belonging to the HSPs family, many research groups have discussed the involvement of HSPs in the meat tenderizing process, without considering their singularities.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple regression analyses were also performed with the combination of four muscle biochemical traits (Intramuscular fat content, mean fiber area, total collagen content and collagen solubility) previously shown [38] to be associated with beef quality. The proportion of the variability in tenderness which is explained by the combination of the 5 groups of probes is indicated (R 2 ) as well as the associated P value.…”
Section: Resultsmentioning
confidence: 99%
“…The four muscle biochemical traits (Intramuscular fat content, mean fiber area, total collagen content and collagen solubility) previously shown to be associated with beef quality [38] were analysed with a similar approach alone or in association with the 5 groups of probes ( DNAJA1, HspH1, HspA8, plus two groups of probes for HspB1- Hsp27). The pooled relationship between muscle characteristics and gene expression with beef tenderness was calculated across animal groups after removing the gender and the year effects, i.e.…”
Section: Resultsmentioning
confidence: 99%